Anteseden Peran Influencer Dalam Consumer Purchase Intention Pada Platform Media Social Instagram - Sari, Cindy Alifia; Hidayat, Anas (Universitas Negeri Padang, 2025)
Influencers are a digital marketing channel that is now widely used by marketers by utilizing their influence in social media to advertise a product. This study objectives to examine the influence of customer experience, trust and perceived value which ultimately affect consumer purchase intention in social media influencer marketing in Indonesia. Data was collected by distributing online questionnaires to 250 respondents via google form using convenience sampling technique. This research was processed with SPSS and PLS-SEM (SmartPLS) applications. The criteria for respondents in this study are aged 17 years and over who are users of the Instagram platform and follow the fadil jaidi influencer account on Instagram. The results of this study indicate that customer experience significantly affects consumer purchase intention, with influencer trust and perceived value acting as mediators. This study found that a positive experience with a trusted influencer can increase purchase intention, and the perceived value of an influencer's recommendation has a positive impact on purchase intention